2021
DOI: 10.1093/bjc/azab043
|View full text |Cite
|
Sign up to set email alerts
|

Police Union Political Communications in Canada

Abstract: The political communications of police unions in the digital age deserve more attention from criminologists. This article examines the communications of two Canadian police associations in Toronto and Winnipeg. Using multimodal discourse analysis, we describe how police unions tactically engage with multiple forms of media to disseminate strategic narratives that reflect police identity and ideology. We conceptualize the mobilization of ‘thin blue line’ narratives and maintenance of a ‘blue wall of silence’ as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In order to address their hybrid professional environment, and the uncertainty and legitimacy pressures derived from it (Minkoff, 2002), parole decision-makers constantly negotiate their time and space and, by doing so, expand their boundary-making tool-kit (e.g. Duncan and Walby, 2021;Quinn, 2020;Young, 2020). The study found three primary conceptualizations of this work: one regarding time and two regarding space.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In order to address their hybrid professional environment, and the uncertainty and legitimacy pressures derived from it (Minkoff, 2002), parole decision-makers constantly negotiate their time and space and, by doing so, expand their boundary-making tool-kit (e.g. Duncan and Walby, 2021;Quinn, 2020;Young, 2020). The study found three primary conceptualizations of this work: one regarding time and two regarding space.…”
Section: Discussionmentioning
confidence: 90%
“…One of the few related studies explored the boundary-work of criminal justice policy-makers in connection with police forensic professionals and judicial professionals by constructing particular understandings of valid knowledge and how it should be produced (Machado and Granja, 2019). A more recent study examined the police unions' boundary-making with the public media for sidestepping critical views of authorities and community activists (Duncan and Walby, 2021). Another study looked at penal sector volunteers' work to distinguish between their 'helper positions' and the positions of other professionals through different discursive frames and rehabilitative ethos (Quinn, 2020).…”
Section: Boundary-work In Professional Organizationsmentioning
confidence: 99%
“…Several communications demonstrate that @StamatakisCPA is opposed to the current municipal government in Vancouver, going so far as to retweet a message calling for a snap election. 14 @StamatakisCPA frequently engages in combative rhetoric with journalists (also see Duncan & Walby, 2022). 15 The partisanship shown by these tweets demonstrates an indiscretion similar to what was described by Goldsmith (2015) on the mishandling of police data.…”
Section: Methodsmentioning
confidence: 99%
“…In Canada, literature to date has similarly observed that police use multiple strategies on Twitter and other social media sites to curate their image and to manage public views of police work (Walby & Joshua, 2021; Walby & Gumieny, 2020; O’Connor, 2017; Schneider, 2016). Public police communicate and create their own images online in part because of ongoing tensions with news media (Duncan & Walby, 2022; Ellis & McGovern, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation